2000
DOI: 10.1039/b005431n
|View full text |Cite
|
Sign up to set email alerts
|

The central ‘relay’ unit in hydraphile channels as a model for the water-and-ion ‘capsule’ of channel proteins

Abstract: The central relay of hydraphile channels is a model for the central ion-capsule of the KcsA K1 K + -conducting channel of Streptomyces lividans; organization of water and concomitant electrostatic stabilization of a transient K + appear to be the functions in both cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 17 publications
(13 reference statements)
1
41
0
1
Order By: Relevance
“…It thus seemed likely that the central relay macrocycle was parallel to the fatty acid chain axis rather than parallel to the membrane surfaces. Additional studies confirmed this assumption and suggested that the central relay interacts with the solvated cation rather than the cation itself [58].…”
Section: Defining the Conformation In The Bilayermentioning
confidence: 84%
See 1 more Smart Citation
“…It thus seemed likely that the central relay macrocycle was parallel to the fatty acid chain axis rather than parallel to the membrane surfaces. Additional studies confirmed this assumption and suggested that the central relay interacts with the solvated cation rather than the cation itself [58].…”
Section: Defining the Conformation In The Bilayermentioning
confidence: 84%
“…The successful function of channels having central relay units [58] too small (e.g. 3) to pass Na + , strongly suggested that in 1, the third macrocycle was positioned perpendicular to the other two and parallel to the axes of the fatty acid chains.…”
Section: 31mentioning
confidence: 99%
“…4,13-Diaza-18-crown-6 was then treated with an excess of the dibromopropoxynaphthalene in the presence of Na 2 CO 3 and catalytic KI. Br(CH 2 ) 3 OC 10 H 6 O (CH 2 ) 3 〈N18N〉(CH 2 ) 3 OC 10 H 6 O(CH 2 ) 3 Br was obtained in 40% yield. This dibromide was treated with 2 equiv of N-dodecyl-4,13-diaza-18-crown-6 to give 5 (13%) as a nearly colorless solid, mp 103-104.5 °C.…”
Section: Compounds Used In This Studymentioning
confidence: 97%
“…20 The phospholipid were obtained as CHCl 3 solutions, which were dried to lipid films and stored under vacuum at ambient temperature. The vesicles were prepared by dissolving a dry lipid film in 0.3 mL diethyl ether and 0.3 mL buffer (750 mM NaCl/15 mM N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid (HEPES), pH 7.0).…”
Section: Vesicle Preparationmentioning
confidence: 99%
“…Extensive studies have characterized the headgroup position [24] and function [25], the orientation [26] of the central macrocycle, and the channel's aggregation state within the phospholipid bilayer [27]. As noted above, linking the sidechains improved ionophoretic activity.…”
Section: Introductionmentioning
confidence: 95%